Dasar-Dasar Kitabah - Kusnawan, Aep (Prophetica, 2009)
Spread of mass media on these current days, especially printed media, such as newspapers, tabloids and magazines, bulletin and books is one of the indicators of information era. Billion of information delivers every time. This phenomenon has raised some opinion. Will we always place ourselves as consumer only? Why dont shift to be a producer? One step to be a producer we can reach is being a writer who will become source of any in formation we can share with others.(Penyebaran media masa saat ini, khususnya media cetak, seperti surat kabar, tabloid dan majalah, buletin serta buku adalah salah satu indikator dari era informasi. Jutaan informasi disampaikan setiap hari. fenomena ini meningkatkan opini. Akankah kita selalu menempatkan diri kita hanya sebagai konsumen? kenapa kita tidak merubah diri menjadi produser? salah satu tahap menjadi produser bisa kita capai dengan menjadi penulis yang akan menjadi sumber dari informasi dimana kita berbagi informasi dengan orang lain.)